PAFAH1B1 and the lncRNA NONHSAT073641 maintain an angiogenic phenotype in human endothelial cells. (20th May 2016) - Josipovic, I.; Fork, C.; Preussner, J.; Prior, K‐K.; Iloska, D.; Vasconez, A. E.; Labocha, S.; Angioni, C.; Thomas, D.; Ferreirós, N.; Looso, M.; Pullamsetti, S. S.; et al.
Abstract: Aim: Platelet‐activating factor acetyl hydrolase 1B1 (PAFAH1B1, also known as Lis1) is a protein essentially involved in neurogenesis and mostly studied in the nervous system. As we observed a significant expression of PAFAH1B1 in the vascular system, we hypothesized that PAFAH1B1 is important during angiogenesis of endothelial cells as well as in human vascular diseases. Method: The functional relevance of the protein in endothelial cell angiogenic function, its downstream targets and the influence of NONHSAT073641, a long non‐coding RNA (lncRNA) with 92% similarity to PAFAH1B1, were studied by knockdown and overexpression in human umbilical vein endothelial cells (HUVEC). Results: Knockdown of PAFAH1B1 led to impaired tube formation of HUVEC and decreased sprouting in the spheroid assay. Accordingly, the overexpression of PAFAH1B1 increased tube number, sprout length and sprout number. LncRNA NONHSAT073641 behaved similarly. Microarray analysis after PAFAH1B1 knockdown and its overexpression indicated that the protein maintains Matrix Gla Protein (MGP) expression. Chromatin immunoprecipitation experiments revealed that PAFAH1B1 is required for active histone marks and proper binding of RNA Polymerase II to the transcriptional start site of MGP. MGP itself was required for endothelial angiogenic capacity and knockdown of both, PAFAH1B1 and MGP, reduced migration. In vascular samples of patients with chronic thromboembolic pulmonary hypertension (CTEPH), PAFAH1B1 and MGP were upregulated. The function of PAFAH1B1 required the presence of the intact protein as overexpression of NONHSAT073641, which was highly upregulated during CTEPH, did not affect PAFAH1B1 target genes. Conclusion: PAFAH1B1 and NONHSAT073641 are important for endothelial angiogenic function.